Latin-Byzantine artistic interactions and the church of Saint Basil in Mržep (Montenegro) - Bacci Michele (Balcanica)
The present paper offers some thoughts on and a new interpretive frame of the painted program of the small, single-nave church of Saint Basil in Mržep, in the vicinity of Donji Stoliv, in the Vrmac peninsula near Kotor, Montenegro. This monument stands out for the abundance of available information on its history, including the name of the painter (Mihailo), the identity of the donor (Stefan Kalođurđević) and even the date of its construction and pictorial decoration (1451). Nevertheless, the art-historical debate has been mostly puzzled by the melange, Latin-Byzantine character of the painted images, which has been explained as an outcome of the Union of the Orthodox and Roman churches declared at the Council of Ferrara-Florence in 1438-1439. The analysis provided here emphasizes the scarcity of indications about the impact of the latter’s resolutions on the arts and proposes an alternative interpretation that associates the choice of specific forms with the devotional strategies worked by Stefan Kalođurđević for his and his family’s spiritual health.